In vitro evaluation of the inhibitory activity of essential oils from lippia origanoides h.b.k. on mycelial growth and sclerotial production of sclerotium cepivorum berk. (2011)
Essential oils obtained from leaves and fiowers of different samples of Lippia origanoides cultivated un- der the environmental conditions of the Cauca Valley, Colombia, were tested in vitro against mycelial growth and sclerotial formation in Sclerotium cepivorum, the pathogen responsible for onion white rot. 9ll the evaluated oils in concentrations ranging from 250 to 1350 iL/L exhibited inhibitory activity against both the mycelium and sclerotia of the pathogen. However, those corresponding to the chemo- type ( )minimum inhibitory concentration, 4(/ 5 120 iL/L8 reached the strongest inhibition results regarding the evaluated pathogen structures. Hence, the chemotype I of L. organoides can be said to have potential inhibitory activity against onion white rot.